2020
DOI: 10.1002/hed.26454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating compliance with process‐related quality metrics and survival in oral cavity squamous cell carcinoma: Multi‐institutional oral cavity collaboration study

Abstract: Background: Process-related measures have been proposed as quality metrics in head and neck cancer care. A recent single-institution study identified four key metrics associated with increased survival. This study sought to validate the association of these quality metrics with survival in a multi-institutional cohort. Methods: Multicenter retrospective study of patients with oral cavity squamous cell (1/2005-1/2015). Baseline patient and disease characteristics and compliance with quality metrics was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For HNCs, identifying and evaluating quality of care metrics is important because they can impact patient outcomes. Process‐related quality metrics (eg, lymph node yield [LNY], guideline adherence 8‐10 ) are modifiable measures associated with the care patients receive from health care providers and systems. Graboyes and colleagues identified 4 quality metrics for oral squamous cell carcinoma (OSCC) and found that compliance correlated to improved survival, highlighting the utility of targeting quality metrics to improve patient outcomes 9,10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For HNCs, identifying and evaluating quality of care metrics is important because they can impact patient outcomes. Process‐related quality metrics (eg, lymph node yield [LNY], guideline adherence 8‐10 ) are modifiable measures associated with the care patients receive from health care providers and systems. Graboyes and colleagues identified 4 quality metrics for oral squamous cell carcinoma (OSCC) and found that compliance correlated to improved survival, highlighting the utility of targeting quality metrics to improve patient outcomes 9,10 …”
mentioning
confidence: 99%
“…Graboyes and colleagues identified 4 quality metrics for oral squamous cell carcinoma (OSCC) and found that compliance correlated to improved survival, highlighting the utility of targeting quality metrics to improve patient outcomes. 9,10 Provision of high-quality care is critical for patient outcomes and of interest to hospitals and national organizations. Studies report substantial variability in the quality of HNC care delivered across US hospitals.…”
mentioning
confidence: 99%
“…A fter undergoing surgical resection, patients with oral cavity squamous cell carcinoma (OCSCC) frequently require adjuvant radiation therapy that considers several known risk factors, such as distance to margins and positive surgical margins. 1,2 However, the optimal method for accomplishing intraoperative margin assessment, either from the tumor bed (defect-driven sampling) vs from the resected en bloc specimen (specimen-driven sampling), is not well defined.…”
mentioning
confidence: 99%